Quality of Clinical Trials — A Concern of Three Decades - Hemminki, Elina (Methods of Information in Medicine, 1982)
The purpose of this article is to summarize reviews on the quality of clinical trials. Altogether 29 reviews were found. Most clinical trials were judged to be uncontrolled or poorly controlled and/or otherwise poor. To study any change over time, reviews based on reports published 1943—1959, 1960—67, and 1968—77 were considered. The proportion of controlled trials was higher in 1943—59 than in 1968—77. The proportion of trials defined as »good« was lowest in the period 1960—1967. Since the material and definitions varied from one review to the other, the results should be interpreted to reflect the reviewers’ concern about quality rather than the actual quality of the trials themselves. In fact, in most reviews, in which the criteria and material used over time were comparable, the quality of trials had improved. But various factors guarantee that worries about the quality of clinical trials will continue.
Keywords: Clinical Trials; Evaluation Study; Review